Four New Sesquiterpenoids from the Roots of Diarthron Tianschanica with Their Antineoplastic Activity - Dong-Xue Sun; Dan Zhao; Hong-Yan Wei; Xiao-Ling Ma; Lei-Ling Shi; Jing Zhang (Molecules, 2018)
Four new sesquiterpenoids, known as diarthronchas A–D (1–4), and one known daphnauranol B (5) were isolated from the methanol extract of the roots of Diarthron tianschanica. The compounds structures were determined on the basis of spectroscopic data. All of the isolated compounds were profiled for their antineoplastic activity.